Satisfação do paciente como indicador da qualidade do serviço de saúde no âmbito hospitalar - Parcianello, Márcio Kist (2023)
Patient satisfaction is understood as a measure of the perception of whether the service and/or overall experience falls short of, meets, or exceeds their expectations. This research aimed to evaluate the level of satisfaction of patients admitted to a large, reference, high-complexity university hospital in the interior of Rio Grande do Sul. This is a cross-sectional study, carried out in the open adult admission units of the hospital, more specifically in the medical, surgical, gynecology and obstetrics, and nephrology admission units. The sample consisted of 158 patients, hospitalized for more than 48 hours, and over 18 years of age, who freely agreed to participate in the research. Data collection occurred through a questionnaire prepared for this purpose, starting in January 2021 and ending in February 2022. In the data analysis, descriptive and inferential analysis was performed using the software Statistic 9.0 and the software R version 4.2.2. The significance level adopted was 5%. Ethical aspects were observed according to the precepts established in Resolution 466/2012 of the Conselho Nacional da Saúde, approved by CAAE 43597421.7.0000.5346. Of the 158 inpatients, most presented a mean of 4.9 concerning the score of more or less satisfied and very satisfied, configuring that, in general, they were very satisfied with the care of the physical therapy, psychology, Nutrition, and social service teams, with emphasis on the care of nutritionists and social service. The factors by which the patients were most satisfied with the care provided by the physical therapists and psychologists were the items of care provided and trust. The nutritionists stood out for their assistance, and the social service was pointed out for being the professional with the best understanding of communication. When evaluated about the medical and nursing staff, in the inpatient unit, it was evident that, in general, the patients were satisfied with the care received, although there were some items pointed out as inadequate by the patients that left them dissatisfied. Thus, in the Surgical Unit, the patients were dissatisfied with the medical professionals regarding information about the treatment, their health status, and the procedures that were performed. In the Gyneco-obstetrics unit, the patients were dissatisfied with the nursing professionals due to problems in understanding the communication used by these professionals. When evaluated about the factors that influenced the satisfaction with the nursing team assistance, the best rated was when they felt pain and/or discomfort (91.77%). For the medical team's assistance, the factors that stood out positively were problem-solving, level of confidence, and service (88.6%). From the results, we concluded that patients admitted to this hospital had high levels of satisfaction with the care received during hospitalization. Thus, it was concluded that predominantly the level of satisfaction of patients was high, indicating that they were very satisfied with the care received during hospitalization, which is directly linked to the level of quality of care provided by different sectors, and thus an indicator of the quality of care provided in this institution.